THU0534 Interleukin-12B is Up-Regulated by Decoy Receptor 3 Specifically in Rheumatoid Synovial Fibroblasts. (10th June 2014) - Fukuda, K.; Miura, Y.; Maeda, T.; Hayashi, S.; Kurosaka, M.
Abstract : Background: Decoy receptor 3 (DcR3) is a secreted decoy tumor necrosis factor receptor (TNFR) and competitively binds and inhibits the TNF family including Fas-ligand (FasL), LIGHT, and TL1A. DcR3 is overexpressed in tumor cells and might benefit tumors by helping them to avoid cytotoxic and regulatory effects of the ligands. We previously reported that DcR3 overexpressed in rheumatoid synovial fibroblasts (RA-FLS) stimulated by TNF-alpha protects the cells from Fas-induced apoptosis [1]. Meanwhile, recent studies suggested that DcR3 directly induces osteoclast formation from monocytes, and that DcR3 triggers enhanced adhesion of monocytes via reverse signaling. We recently reported that DcR3 induces VLA-4 expression in THP-1 macrophages to inhibit cycloheximide-induced apoptosis [2], and that DcR3 binds to TL1A expressed on RA-FLS resulting in the negative regulation of cell proliferation induced by inflammatory cytokines [3]. Further, we newly reported the microarray data analysis revealed DcR3 regulates gene expression in RA-FLS. The profiles indicated shared interleukin (IL)-12B p40 subunit of IL-12 and IL-23 was up-regulated by DcR3 (fold change 1.65) [4]. Objectives: In this study, we analysed IL-12B expression in RA-FLS stimulated with DcR3 in detail. Methods: Real-time polymerase chain reaction (real-time PCR). RA and osteoarthritis (OA) -FLS were stimulated with various concentration of DcR3-Fc or control IgG1 for 12 hours. Further, RA-FLS were incubated with DcR3-Fc for 12 hours after overnight pre-incubation with anti-TL1A antibody. The relative expression levels of IL-12B mRNA were quantified by real-time PCR. Western blotting. RA-FLS was stimulated with 1000 ng/ml DcR3-Fc or control IgG1 for 24 hours. The expression of IL-12B p40 protein in RA-FLS was investigated by western blotting. Results: Real-time PCR. Real-time PCR revealed that DcR3-Fc significantly increased the expression of IL-12B mRNA in RA-FLS in a dose dependent manner (113% with 10ng/ml, 135% with 100ng/ml, and 218% with 1000ng/ml) compared with control IgG1. In contrast, DcR3-Fc did not increase IL-12B mRNA in OA-FLS. Anti-TL1A antibody inhibited the up-regulation of IL-12B expression in RA-FLS induced by DcR3-Fc. Western blotting. Western blotting confirmed that IL-12B p40 protein in RA-FLS was increased when stimulated with DcR3-Fc. Conclusions: IL-12 consisted of IL-12A (p35) and IL-12B induces Th1 immune responses to be linked with autoimmune diseases including psoriasis and inflammatory bowel disease. Meanwhile, IL-23 consisted of IL-23A (p19) and IL-12B is involved in the inflammatory pathway and linked to multiple sclerosis and inflammatory bowel disease [5]. In this study, we revealed that DcR3 increased the expression of IL-12B in RA-FLS in a disease-specific fashion by binding to membrane-bound TL1A as a ligand. DcR3 may affect the pathogenesis of RA through IL-12B. References: Hayashi S. et al., Arthritis and Rheum, 56, 1067-1074, 2007 Tateishi K. et al., Biochem Biophys Res Commun, 389, 593-598, 2009 Takahashi M. et al., Int J Mol Med, 28, 423-427, 2011 Fukuda K. et al., Int J Mol Med, 32, 910-916, 2013 Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.3991